Гомологічна рекомбінація у гетерозиготних за мейотичними мутаціями рослин томату - Лісовська, Т.П. (Фактори експериментальної еволюції організмів, 2015)
Signifi cant progress in understanding the genetic control of meiosis and crossing-over, in particular, was obtained through research eukaryotic mutant organisms that violate the normal course of meiosis, called meiotic mutants. The article presents the results of estimating the frequency of crossing-over in four heterozygotes for meiotic mutations tomato. Methods. The infl uence of mei-genes on recombination frequency was performed using lines that contain marker genes in the 2nd (wv, aw, d), 4th (e, ful), 6th (m-2, c) and 11 (hl, a) chromosomes. Sex difference in rf was determined on the basis of splitting of marker signs in populations F2 and testcrosses of Fl as maternal form with multiple-marker tester. Expected value of rf the maximum likelihood method. Results. Mutations in the heterozygous state did not affect signifi cantly the frequency of crossing-over in marked areas of the genome according to F2, except heterozygotes As1/ as1, which revealed rf reduction in area wv-aw. Assessment crossover frequency separately in female and male meiosis showed that in control — the initial variety Gloria and heterozygote Dsm1/dsm1 crossover frequency is higher in male meiosis (microsporogenesis) in heterozygotes Sti/sti rf frequency was signifi cantly higher in female meiosis. Conclusions. The meiotic mutation as1 and stі is recessive completely by cytological manifestation, but not completely recessive to infl uence the homologous recombination. Keywords: meiotic mutants, heterozygotes, crossing over, sex difference, tomato.